Cellular promiscuity: explaining cellular fidelity in vivo against unrestrained pluripotency in vitro. (11th December 2012) - Schatten, Gerald
Abstract : The differentiation of pluripotent stem cells into various progeny is perplexing. In vivo, nature imposes strict fate constraints. In vitro, PSCs differentiate into almost any phenotype. Might the concept of 'cellular promiscuity' explain these surprising behaviours?